Delta Inferior Vena Cava Index Correlated with Mean Arterial Pressure (MAP) in Spinal Anesthesia - Wiwi Jaya; Ulil Abshor; Buyung Hartiyo Laksono; Arie Zainul Fatoni (Journal of Anaesthesia and Pain, 2021)
Background: Spinal anesthesia has become an alternative to general anesthesia. However, spinal anesthesia has the most common side effects including, bradycardia and hypotension. The aim of this study was to determine the relationship between changes in the inferior vena cava index (delta inferior vena cava index) to changes in mean arterial pressure in spinal anesthesia.Methods: This study was an observational pre-post test study in thirty-two patients who received spinal anesthesia. The inferior vena cava index (inferior vena cava collectibility index and caval-aorta index) was measured before and after spinal anesthesia (5 and 10 minutes after onset). Data were analyzed using the Kolmogorov Smirnov test, Shapiro-Wilk test, T-test, and correlation test with α=5%Result: There was a significant difference in mean arterial pressure (MAP), delta inferior vena cava collectibility index (D-IVC-CI), and delta caval-aorta index (D-CAo-I) before and after spinal anesthesia. D-IVC-CI and D-CAo-I are significantly correlated with MAP. The correlation between D-IVC-CI and MAP had R = -0.371 (P <0.05) at 5 minutes post-anesthesia, while D-CAo-I and MAP had R = 0.472 (P <0.05) at 10 minutes post-anesthesia. Conclusion: The delta inferior vena cava index is correlated with the mean arterial pressure (MAP) value in spinal anesthesia.